Pharmacokinetics, pharmacodynamics, and safety of pasireotide LAR in patients with acromegaly: A randomized, multicenter, open‐label, phase I study. (24th May 2014) - Petersenn, Stephan; Bollerslev, Jens; Arafat, Ayman M.; Schopohl, Jochen; Serri, Omar; Katznelson, Laurence; Lasher, Janet; Hughes, Gareth; Hu, Ke; Shen, George; Reséndiz, Karina Hermosillo; Giannone, Vanessa; et al.
Abstract Pasireotide (SOM230), a multireceptor‐targeted somatostatin analogue, has exhibited favorable safety/tolerability in several clinical studies. A long‐acting‐release (LAR) formulation of pasireotide may offer advantages over the subcutaneous formulation. This randomized, open‐label, Phase I study evaluated the safety, PK, and PD of pasireotide LAR 20, 40, or 60 mg/month in patients with acromegaly. Safety assessments and blood samples for PK and PD were taken at designated time points. Thirty‐five patients were randomized and completed the study. Steady‐state pasireotide concentrations were achieved following three monthly injections. Trough pasireotide concentrations (ng/mL) 28 days after each injection were: 2.48, 4.16, and 3.10 (20 mg group); 6.42, 6.62, and 7.12 (40 mg group); and 9.51, 11.7, and 13.0 (60 mg group). At study end, 51% and 57% of patients achieved GH levels ≤2.5 μg/L and IGF‐1 levels below ULN, respectively. Compared with baseline, fasting blood glucose and HbA1c levels increased, whereas fasting blood insulin levels decreased. Acromegaly symptoms were generally improved. Adverse events were mostly gastrointestinal and mild/moderate. Pasireotide LAR was generally well tolerated. Steady‐state PK was achieved after three monthly doses; exposures were approximately dose proportional. Control of GH, IGF‐1, and symptoms improved, suggesting that pasireotide LAR may be an effective treatment for acromegaly.